Audit Energi dan Rekomendasi Penghematan Energi Listrik di Gedung Rumah Sakit - Muhammad Fahmi Hakim; Ahmad Hermawan; Fandi Kurniawan; Kumala Mahda Habsari (Politeknik Negeri Malang, 2023)
The actions for electricity consumption more efficiently is reducing the amount of electricity consumption of renewable and non renewable energy for human living sustainability or we can called energy conservation. Energy audit purposed to the energy utilization evaluation progress, is still infrequently applied in Indonesia, especially in huge building. The analyzing result of A building in the Dr. Radjiman Wediodiningrat Asylum, the first value audit of Energy Use Intensity (EUI) is 21,944 kwh/m2/year it was include the criteria of efficient. This EUI value is below EUI research that was issued by ASEAN-USAID in 1992 and the EUI value average of hospital in Korea, while detailed audit obtained energy value of EUI is 23,213 kWh/m2/year is included to the criteria of efficient. The THDi value in electricity system is IR= 33,2%, IS=24,48%, IT= 34,85% and IN=122,96%, the THDi value is not complied with IEEE 519-2014 permission which is the value is ISC/IL> 1000 has restraint value by 20%. Whereas the THDv value in electricity system is VR-S= 2,04%, VS-T= 2,11%, VT-R= 1,97%, VR-N= 3,83%, VS-N= 3,69%, VT-N= 3,73% and VL-L= 2,04% and VL-N= 3,75%, the value of THDv is complied the permissiod by IEEE 519-2014 with Voltage system of identification by 0,4 kV, therefore the limit value of THDV which permitted is 8%.